The future of the self an interdisciplinary approach to personhood and identity in the digital age - Friedenberg, Jay (University of California Press, 2020)
"This book is about who we are and who we might be, given our current and future interactions with technology. It delves into what a person is as well as what a person might become. It is also about the descriptions we provide for ourselves, what we call our self or identity. These are complex topics and have been addressed from many different disciplinary perspectives. As a result we discuss them from the point of view of philosophy, psychology, neuroscience, artificial intelligence and robotics. The central argument put forth here can be stated in three parts. (1) There is no difference between what we call natural and artificial systems because all systems are made up of matter and energy and are governed by universal physical laws. (2) Sufficient understanding of a system in the form of description, explanation, and prediction allows us to replicate or reproduce it. (3) Exact or functionally equivalent reproductions of an original system will exhibit similar behavior. If these three propositions are true then the existence of an artificial self is possible. These are very controversial statements and there are quite a few objections to them. This book is divided into four main sections. The first section includes this introduction along with a chapter on the philosophy of self and a chapter on the psychology of self. These three chapters together provide a summary of historical and contemporary thought on personhood, self, and identity. They serve as a foundation upon which the remaining parts of the book rest. The second section consists of three chapters. These are titled in order: The Brain, The Brain + Hardware, and The brain + Software. These topics can be thought of as concentric rings of self that radiate outward from the brain and body to include prosthetics and robotics (hardware) and then computer programs and artificial intelligence (software). In the third section there are four chapters. The first is on avatars, which are software manifestations of self. The second is on virtual worlds, which are the environments that avatars inhabit. The third is on software selves, beings that might exist as entirely electronic. The fourth chapter of this section that concludes the book is more speculative and describes what future selves might be like. Most of what we present up until this point is factual or plausible, based on scientific research or near term future predictions. But in the last chapter all bets are off. There we speculate on what might occur either within the next century or beyond. We live in exciting times where technology is accelerating exponentially. Many of us will live to see some of these ideas realized"--